Unidirectional hybridization between American paddlefish Polyodon spathula (Walbaum, 1792) and sterlet Acipenser ruthenus (Linnaeus, 1758) - Jenő Káldy; Georgina Fazekas; Balázs Kovács; Mariann Molnár; Bence Lázár; Nóra Pálinkás-Bodzsár; Uroš Ljubobratović; Gyöngyvér Fazekas; Gyula Kovács; Eszter Várkonyi (PeerJ, 2024)
Interspecific hybridizations among sturgeon species are feasible and often bidirectional. The American paddlefish (Polyodon spathula) from Family Polyodontidae and sturgeon species from Family Acipenseridae were reported capable of hybridization, but viable hybrids have been described only in crosses with the American paddlefish as paternal parents. In the reciprocal cross, the hybrids were not viable however embryos start to develop and reach late gastrula and early neurula stages. The goal of this study was to examine the hybridization between the sterlet sturgeon (Acipenser ruthenus) and the American paddlefish. Hybrid and purebred crosses were produced by artificial fertilization. Viable hybrid offspring were harvested (three month old) and verified in the families produced by female sterlet crossing with male American paddlefish. In the reciprocal hybrid crosses with female American paddlefish and male sterlet, the embryos development did not pass over 120 h post fertilization, indicating the unidirectional hybridization between American paddlefish and sterlet. Chromosome counting showed for the same ploidy level of viable hybrid and parent species. Analysis of three microsatellite markers confirmed the unidirectional hybridization between the American paddlefish and the sterlet species. Overall, the inferred genetic cause suggests that unidirectional hybridization between American paddlefish and sterlet may be the case not only for these two species but likely also between American paddlefish and other sturgeon species.